A phase III randomised study comparing concomitant radiochemotherapy with cisplatin and docetaxel as induction versus consolidation treatment in patients with locally advanced unresectable non-small cell lung cancer. (March 2018) - Sculier, Jean-Paul; Lafitte, Jean-Jacques; Berghmans, Thierry; Meert, Anne-Pascale; Scherpereel, Arnaud; Roelandts, Martine; Van Cutsem, Olivier; Colinet, Benoit; Bonduelle, Yves; Giner, Vicente; Paesmans, Marianne; Leclercq, Nathalie; et al.
Highlights: Concurrent radiochemotherapy is the recommended treatment for unresectable stage III NSCLC. There is no survival difference between induction and consolidation radiochemotherapy. The cisplatin + docetaxel regimen gives good 2-year (44%) and 5-year (∼25%) survivals. The role of consolidation or induction chemotherapy remains to be defined. Abstract: Objectives: To assess if induction radiochemotherapy followed by consolidation chemotherapy (arm A) will improve survival in comparison with the same chemotherapy given as induction followed by consolidation concurrent radiochemotherapy (arm B) in patients with unresectable non-metastatic non-small cell lung cancer (NSCLC). Patients and methods: Chemotherapy consisted in a combination of cisplatin with docetaxel, with one initial course for each patient, two courses in single modality therapy and weekly administration during chest irradiation (66 Gy). Results: A total of 125 patients were randomised before early closure of the study because of poor accrual and an unplanned blind interim analysis which suggested that the continuation of the study would have been futile. Mature survival results showed no significant difference between both modalities with median survival times, respectively in arms A and B, of 19.6 months and 18.3 months, two years survival rates of 44% and 44% and five years survival rates of 23% and 26%. Toxicity was acceptable. Conclusions: Our randomised study did not demonstrate survival difference between induction concurrent radiochemotherapy followed by consolidation chemotherapy and induction chemotherapy followed by consolidation concurrent radiochemotherapy.